Reaction of 2-Diazo-1,2-diphenylethanone with 2-[(Arylimino)methyl]phenols - Pheko, Tshepo; Singh, Girija S. (Letters in Organic Chemistry, 2006)
An equimolar reaction of the 2-diazo-1,2-diphenylethanone with 2-[(arylimino)methyl]phenols affords 2-[(arylimino)methyl]phenyl-2,2-diphenylacetates and 2-azetidinones. The products have been characterized on the basis of satisfactory spectral data. The regiochemistry of the reaction of hydroxyl and imino group towards diphenylketene, generated from thermal decomposition of the 2-diazo-1,2- diphenylethanone, has been observed to depend on the substituents on N-phenyl ring.
Keywords: diphenylketene